The Effect of Going Concern Opinions on Stock Prices With Auditor Reputation as A Moderator - Dewantoro, Wisnu Ari; Rustam, Akie Rusaktiva (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
An important consideration for investors before making investment decisions is that going-concern audit opinion is a critical warning about the company's future viability. This research is a quantitative study with a causal study approach. As such, this research examines the effect of going-concern audit opinions on stock prices with auditor reputation as a moderating variable. The samples include 128 data from 32 manufacturing companies listed on the Indonesia Stock Exchange between 2019 and 2022, selected through purposive sampling. The purposive sampling method was used to obtain a representative sample meeting the testing criteria, ensuring that the analysis results could address the research problem. Furthermore, the results of the hypothesis testing using Linear Regression Analysis and Moderated Regression Analysis (MRA) exhibit that going-concern audit opinion negatively affects stock prices, and the auditor's reputation cannot moderate the effect of going-concern audit opinion on stock prices. Abstrak Opini audit going concern dapat menjadi pertimbangan penting bagi investor sebelum melakukan keputusan investasi karena opini audit going concern dapat menjadi peringatan penting mengenai kelangsungan hidup perusahaan di masa depan. Penelitian ini dilakukan untuk menguji pengaruh penerimaan opini audit going concern terhadap harga saham dengan reputasi auditor sebagai variabel pemoderasi. Penelitian ini menggunakan metode purposive sampling dengan total sampel 128 yang terdiri dari 32 perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode tahun 2019-2022. Hasil pengujian hipotesis menggunakan Analisis Regresi Linier Sederhana dan Moderated Regression Analysis (MRA) menunjukkan bahwa penerimaan opini audit going concern berpengaruh negatif terhadap harga saham. Sedangkan reputasi auditor sebagai variabel pemoderasi tidak mampu memoderasi pengaruh opini audit going concern terhadap harga saham.